DNA-Segment-Facilitated Dissociation of Fis and NHP6A from DNA Detected via Single-Molecule Mechanical Response. Issue 19 (25th September 2015) - Giuntoli, Rebecca D.; Linzer, Nora B.; Banigan, Edward J.; Sing, Charles E.; de la Cruz, Monica Olvera; Graham, John S.; Johnson, Reid C.; Marko, John F.
Abstract: The rate of dissociation of a DNA–protein complex is often considered to be a property of that complex, without dependence on other nearby molecules in solution. We study the kinetics of dissociation of the abundant Escherichia coli nucleoid protein Fis from DNA, using a single-molecule mechanics assay. The rate of Fis dissociation from DNA is strongly dependent on the solution concentration of DNA. The off-rate ( k off ) of Fis from DNA shows an initially linear dependence on solution DNA concentration, characterized by an exchange rate of k ex ≈ 9 × 10 − 4 (ng/μl) − 1 s − 1 for 100 mM univalent salt buffer, with a very small off-rate at zero DNA concentration. The off-rate saturates at approximately k off, max ≈ 8 × 10 − 3 s − 1 for DNA concentrations above ≈ 20 ng/μl. This exchange reaction depends mainly on DNA concentration with little dependence on the length of the DNA molecules in solution or on binding affinity, but this does increase with increasing salt concentration. We also show data for the yeast HMGB protein NHP6A showing a similar DNA-concentration-dependent dissociation effect, with faster rates suggesting generally weaker DNA binding by NHP6A relative to Fis. Our results are well described by a model with an intermediate partially dissociated state where the protein is susceptible to being captured by a second DNA segment, in the manner of "direct transfer" reactions studied for other DNA-binding proteins. This type of dissociation pathway may be important to protein–DNA binding kinetics in vivo where DNA concentrations are large. Graphical Abstract: Highlights: Protein off-rates from DNA are often modeled as concentration independent. Single-molecule data show dependence of unbinding on DNA concentration. Multi-state dissociation pathway can explain the experimental data.